A NEW BETTLE SPECIES OF THE GENUS TALDYCUPES (TALDYCUPEDIDAE, COLEOPTERA) FROM THE PERMIAN OF THE TUNGUSKA RIVER BASIN - Ponomarenko A.G. (My University, 2006)
Taldycupes rosanovi sp. nov. is described from an isolated elytron from the locality of Ilimpeya, Krasnoyarsk Krai, Tunguska River basin, Limptekon Formation.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская